Profitability as Mediator in Tax avoidance: Evidence from Indonesian Financial Sector - Andora, Andora; Poernamawatie, Fahmi; Orbaningsih, Dwi; Hertanto, Ronny Hendra; Pitalokasari, Nurfilaili Diah (Jurnal Akuntansi, 2025)
This study aims to empirically test whether profitability can mediate the influence of academic qualifications of CFOs and independent commissioners on tax avoidance. The research sample was 62 with a purposive sampling technique in financial sector companies listed on the IDX in 2023. The research method applied is Partial Least Square (PLS) modeling using smartPLS 4.0 software assistance to analyze the data. The results found that H1 was rejected, CFO academic qualifications had no significant effect on tax avoidance. H2 accepted, independent commissioners have a significant effect on tax avoidance. H3 is accepted, CFO academic qualifications have a significant effect on profitability. H4 is accepted, independent commissioners have a significant effect on profitability. H5 accepted, profitability affects tax avoidance. H6 accepted, profitability can mediate the effect of CFO academic qualifications on tax avoidance. H7 accepted, profitability can mediate the effect of independent commissioners on tax avoidance. Firm size as a control variable has no significant effect on profitability and tax avoidance.